O compositor na sala de aula: sonoridades contemporâneas para educação musical - Borges, Alvaro Henrique [UNESP] (2014)
This thesis was developed to lessen the absence of the repertoire of contemporary, experimental and electroacoustic music in the school environment. Contemplated by composer Guy Reibel, this finding, caused by a lack of communicability of some unfamiliar code, was verified through observations and analyses of the “School Music Program” at the City of Pouso Alegre - MG. This program is a demonstration of social and political opportunity, being that since 2005 it provides access to music education in regular schools by a structured process. However it doesn’t address the contemporary repertoire and pedagogical techniques that embrace it. We don’t want to reduce the merits or the relevance of Minas Gerais public policy, which has a differentiated performance if compared to other states in Brazil regarding the teaching of music. The study sought ways to expand the actions already consolidated for greater coverage on performances in the schools. Preliminary observations were focused on some aspects: the origin of the program as a result of public policies and description of its structures and its relationship with the conservatories programs “School Music Program”, as well as its scope in municipal schools. Subsequently, bridges were built to approach the educators of the program to the educational musical repertoire that involves alternative ways to listen and make music following some contributions of the composers-educators from the mid twentieth century, namely Murray Schafer, Guy Reibel, John Paynter, Boris and George Porena Self and others. The structural development process of this research was the educational experiences analysis developed through meetings with the program educators and the researcher, called “Training Workshops”, as well as an analysis of the direct work of the educators in the schools with their students. The main purpose of this procedure was to expand the teach ...